A case of systemic lupus erythematosus presenting with protein-losing enteropathy - Nuran TÜRKÇAPAR,; Nil ÖZYÜNCÜ,; Kubilay ÇINAR,; Arzu ENSARİ,; Özlem KÜÇÜK,; Ramazan İDİLMAN,; Neval DUMAN,; Ali ÖZDEN, (Turkish Journal of Gastroenterology, 2019)
-